Impact of Projects with Future Potential on the Global Competitiveness Index of Countries - Akbota Akzambekkyzy; Laszlo Vasa; Jeffrey Yi-Lin Forrest; Shynara Sarkambayeva; Satyanand Singh (Ital Publication, 2024)
The concept of project success has evolved from the perspective of conforming to the project triangle to that of benefiting the environment, and then from the perspective of the following generation. Scientists increasingly assert that successful projects require a set of criteria that include such item(s) as future potential. The meaning of project success varies depending on where it is executed. The purpose of this study is to identify whether projects with future potential have a certain effect on indicators of the Global Competitiveness Index (GCI) of the Republic of Kazakhstan (RK) and what other success criteria are inherent in such projects. By using the method of descriptive analysis of data collected from 107 experts and analyzing 19 influential projects, the study revealed that projects oriented towards the future have a significant impact on the indicators of the GCI in the RK. This finding confirms the necessity of considering the long-term sustainability and social significance of projects when assessing their successes. Additionally, a specific combination of success criteria that contributes most to this impact was identified. This research provides a brand-new understanding of project success criteria in the context of their impact on the GCI and emphasizes the importance of considering future potential in project planning and evaluation. Doi: 10.28991/ESJ-2024-08-02-012 Full Text: PDF